Beyond QuantiFERON-TB Results, the Added Value of a Weak Mitogen Response - Jacquier, Marine; Binquet, Christine; Manoha, Catherine; Audia, Sylvain; Simonet-Lamm, Anne-Laure; Casenaz, Alice; Sow, Amadou-Khalilou; Piroth, Lionel; Blot, Mathieu (Frontiers in Medicine, 2022)
Introduction While QuantiFERON-TB gold (QFT) is frequently used, little attention is paid to the mitogen response. How it could be impacted and associated with outcomes is poorly known. Methods Retrospective, case-control study in hospitalized patients who underwent QFT testing in two hospitals between 2016 and 2019. We defined two groups of cases with either negative [interferon (IFN)-γ ≤ 0.5 IU/ml, official threshold] or weak (0.5–2 IU/ml) mitogen response, and one group of controls with normal (>2 IU/ml) mitogen response. Results A total of 872 patients were included. An ongoing infection was independently associated with both a negative (RR = 4.34; 95% CI = 2.94–6.41) and a weak mitogen response (RR = 2.44; 95% CI = 1.66–3.58). Among tuberculosis patients, a weak mitogen response was associated with a false-negative QFT result (75%) compared to a normal response (20%). Decreasing mitogen response (normal, weak and negative, respectively) was associated with increasing length of hospital stay [median (interquartile range) 5 (3–13), 11 (5–21) and 15 (10–30) days; p < 0.001] and increasing hospital mortality (3, 7, and 15%; p < 0.001). Conclusion Clinicians should take notice of the mitogen response since IFN-γ concentrations lower than <2 IU/ml were associated with false-negative QFT results in tuberculosis patients, independently associated with ongoing infections, and could be associated with worse prognosis.